Use six Sigma technique to configure the plate ratio of defective units for quality control and compare them with plate ratio of defective units using three Sigma with the application - المدرس دڵشاد محمود صالح; المدرس المساعد هۆشمەند رفيق إبراهيم; المدرس المساعد دەشتى إسماعيل جميل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study was construction Proportion of defective -chart based on SixSigma and comparison with Proportion of defective -chart based on three-Sigma. The study concluded that the Proportion of defective -chart based on sixSigma has better property than Proportion of defective -chart based on threeSigma, because Proportion of defective -chart based on six-Sigma have the smallest control interval, The quality control charts has been drawn by using program (Statgraphics).